2010
DOI: 10.1021/ma101803h
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Structural Polydispersity in Branched Polybutadienes

Abstract: The structural details of a set of highly entangled H-shaped polybutadienes (PBDs) prepared by anionic polymerization were examined in detail by three reputable laboratories using size exclusion chromatography (SEC) and temperature gradient interaction chromatography (TGIC). While SEC data indicated that samples having the desired structures (i.e., nearly monodisperse H-shaped polymer) had been produced, additional SEC data from other laboratories showed that the samples were structurally more complex than ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…The efficiency of the two coupling methods are compared and the 'purified' star polymers characterised by both SEC and Temperature Gradient Interaction Chromatography (TGIC). Whilst SEC has been the characterisation method of choice for many decades, for the analysis of molecular weight and molecular weight distribution of polymers, in recent years TGIC has emerged as a technique capable of significantly enhanced resolution compared to SEC, especially in the characterisation of branched polymers [12,14,[68][69][70][71]] -a subject recently reviewed in detail [72]. In the current work TGIC revealed low levels of heterogeneity in the purified (fractionated) stars -heterogeneity which could not be detected by SEC.…”
Section: Introductionmentioning
confidence: 67%
“…The efficiency of the two coupling methods are compared and the 'purified' star polymers characterised by both SEC and Temperature Gradient Interaction Chromatography (TGIC). Whilst SEC has been the characterisation method of choice for many decades, for the analysis of molecular weight and molecular weight distribution of polymers, in recent years TGIC has emerged as a technique capable of significantly enhanced resolution compared to SEC, especially in the characterisation of branched polymers [12,14,[68][69][70][71]] -a subject recently reviewed in detail [72]. In the current work TGIC revealed low levels of heterogeneity in the purified (fractionated) stars -heterogeneity which could not be detected by SEC.…”
Section: Introductionmentioning
confidence: 67%
“…The primary impediments are that (i) synthesizing well-defined and well-characterized BPs is highly nontrivial [7,[215][216][217][218][219][220][221], (ii) the process of testing and calibrating the rheological models exposes many weaknesses of the tube model that are not manifested for LPs [158,159], and (iii) there is no counterpart to the "double reptation" model because of the complexity of the computational models. Even so, the past few years have seen tremendous progress.…”
Section: Methods and Progressmentioning
confidence: 99%
“…They found rheology to be more sensitive to branching, as expected, but reported that a combination of both the methods resulted in better overall characterization. Some of the works previously referenced also employ multidetector methods [88,219,220,302,315].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The use of model polymers of well-defined architecture is important in probing molecular rheology [1][2][3][4]. Indeed, substantial progress has been made in decoding the linear viscoelasticity of model branched polymers (such as combs or pom-pom-like macromolecules), and more recently their nonlinear response in shear and extension.…”
Section: Introductionmentioning
confidence: 99%